DESIGN AND IMPLEMENTATION OF LOW COST DATA ACQUISITION SYSTEM FOR ECG SIGNAL AND EDR USING LABVIEW AND ARDUINO - HASSAN SALLO, DILSHAD (Journal of Duhok University, 2019)
usage of electrocardiogram (ECG) signals not only limited to the medical services, but also used for studying, learning, processing and analysing. However, the devices such as BIOPAC Systems that used for this purpose are extremely expensive and often not existed, particularly in the third world. The aim of this paper is to design and implement low cost data acquisition system to capture ECG signals and generating ECG-Derived Respiration (EDR) using the LabVIEW platform and Arduino with help of AD8232 chip. The system is designed to monitor the heart signals over the time and calculates the heart rate accurately. It also constructs the breathing signal indirectly by detecting R peaks in ECG signals and interpolating them. Furthermore, this system introduces a unique feature through giving ability to save both the heart and breathing signals as the Matlab file to be used for further analysis. The outcomes show that the ECG signals are in the standard range, as well as constructing breathing signal was successfully done, and the obtained low cost system can be useful for biomedical studies.